Concern and roles of physical planning in local economic development - EMMANUEL, Adebayo Adewunmi; LAWANSON, Olaitan Taibat (2008)

(untitled)
The role of the town planner is changing day by day and this is due to the various challenges being faced by him as the custodian of the environment. The various consultancy services provided by the town planner give a clear picture of this development. This paper identifies consequences of poverty alleviation, the problem of slum development and issues of affordability as some of the causes for concern, on the part of the town planner, for local economic development. It discusses his roles towards achieving local economic development to include the provision of economic services, influencing renewal/regeneration policies and advocacy for the poor among other things. It concludes by saying that town planners in the developed world will find it easier than those in the developing world to face the challenges at hand.